Do aid for trade flows help reduce the shadow economy in recipient countries? - Sèna Kimm Gnangnon (Economies, 2022)
The present analysis assessed the effect of Aid-for-Trade (AfT) flows on the shadow economy using an unbalanced panel dataset of 106 countries over the period of 2002 to 2015. The empirical results obtained by means of the two-step system generalized method of moments showed that higher AfT flows were associated with a decrease in the size of the shadow economy, with less developed countries experiencing a greater negative effect of AfT flows on the shadow economy than relatively advanced countries among recipient countries of AfT flows. AfT interventions reduced the size of the shadow economy in countries that faced high trade costs as well as in those that experienced a depreciation in the real exchange rate. Finally, AfT interventions reduced the size of the shadow economy in countries that improved economic sophistication.
Keywords: F14; F35; O17; 330; Aid for Trade; real exchange rate; shadow economy; trade costs